The Impact of Orthodontic fixed appliance and clear plastic aligner in periodontal health; A comparative clinical study - Sana Akram, Muhammad Zeeshan, Mariyam Masood, Daud Anthoney, Nadia Irshad, Mahrukh Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the periodontal health of patients with fixed orthodontic and clear aligner treatment with a follow-up of three months supportive periodontal therapy. Study Setting: After receiving approval from the hospital’s ethical committee the study was conducted at Department of Dentistry Faryal Dental College, Sheikhupura from September 2021 to February 2022. Material and Methods: For this study 40 individuals were selected and divided them into 2 different groups regarding age and mode of treatment. In Group E, 20 individuals were of age in between 15-30 years and they used multi-bracket fixed therapy while in Group F, 20 individuals of age in between 15- 30 years were used treatment with clear aligners. Results: Results of current study were significant (P < 0.05) regarding logistic regression model of descriptive statistics of dependent variables measured for periodontal therapy after 3 month follow-up respectively. Percentage standard mean deviation (Mean±SD) levels of recovery rate, patient compliance, probing depth, plaque index, bleeding on probing and gingival recession for fixed appliance brackets and clear aligners were (56.21± 11.11, 31.14± 11.11, 13.04± 10.01, 26.10± 3.10, 15.21± 10.12, 01.12± 13.11),( 59.22± 1.01, 43.11± 01.10, 14.01± 11.21, 22.10± 3.10, 6.11± 10.11, 06.12± 14.11) noted respectively. Conclusion: The results of current study were significant (P < 0.05) regarding logistic regression model of descriptive statistics of dependent variables measured for periodontal therapy after 3 month follow-up respectively. Patient compliance with clear aligner treatment was higher than fixed appliance brackets.